Anti-black literacy laws and policies - Willis, Arlette Ingram, author.
1 online resource
Keywords: "This groundbreaking book uncovers how anti-Black racism has informed and perpetuated anti-literacy laws, policies, and customs from the colonial period to the present day. A counternarrative of the history of Black literacy in the United States, the book's historical lens reveals the interlocking political and social structures that have repeatedly failed to support equity in literacy for Black students. Arlette Ingram Willis walks readers through the impact of anti-Black racism's impact on literacy education by identifying and documenting the unacknowledged history of Black literacy education, one that is inextricably bound up with a history of White supremacy. In illuminating chapters, Willis exposes, interrogates, and analyzes incontrovertible historical evidence of the social, political, and legal efforts to deny equal literacy access. Chapters cover an in-depth evolution of the role of White supremacy and the harm it causes in forestalling Black readers' progress; a critical examination of empirical research and underlying ideological assumptions that resulted in limiting literacy access; and a review of federal and state documents that restricted reading access for Black people. Willis interweaves historical vignettes throughout the text as antidotes to whitewashing the history of literacy among Black people in the US and offers recommendations on ways forward to dismantle racist reading research and laws. By centering the narrative on the experiences of Black people in the US, Willis shifts the conversation and provides an uncompromising focus on not only the historical impact of such laws and policies but also their connections to the present-day laws and policies. A definitive history of the instructional and legal structures that have harmed generations of Black people, this text is essential for scholars, students, and policymakers in literacy education, reading research, history of education, and social justice education"--